Cryogenic-temperature-induced structural transformation of a metallic glass - Xilei Bian; Gang Wang; Qing Wang; Baoan Sun; Ishtiaq Hussain; Qijie Zhai; Norbert Mattern; Jozef Bednarčík; Jürgen Eckert (Materials Research Letters, 2017)
The plasticity of metallic glasses depends largely on the atomic-scale structure. However, the details of the atomic-scale structure, which are responsible for their properties, remain to be clarified. In this study, in-situ high-energy synchrotron X-ray diffraction and strain-rate jump compression tests at different cryogenic temperatures were carried out. We show that the activation volume of flow units linearly depends on temperature in the non-serrated flow regime. A plausible atomic deformation mechanism is proposed, considering that the activated flow units mediating the plastic flow originate from the medium-range order and transit to the short-range order with decreasing temperature.